Dynamics of Gratifications Sought from Students During the Online Search for Graduate Programs - Allison R Byrd; Alexa J. Lamm; Jessica Holt; Kevan W. Lamm; Rochelle Sapp (Journal of Applied Communications, 2025)
Recruitment of graduate students into colleges of agriculture (COAs) requires a nuanced understanding of student needs and motivations to strategically communicate scientific information with prospective students. COAs should therefore understand the online, asynchronous tools prospective graduate students use and the needs they expect those tools to fulfill. Using principles of uses and gratifications theory, this study’s purpose was to determine if gratifications sought from departmental websites, faculty lab websites, or social media during the graduate program search process varied based on students’ individual-level cultural dimensions of collectivism/individualism, power distance, and uncertainty avoidance. Quantitative analysis of a survey distributed to graduate students at nine COAs across the U.S. revealed graduate students preferred websites and social media that provided realism and the sense of being at the university. There were significant relationships between respondents’ gratifications sought on departmental websites and faculty lab websites and collectivism, as well as uncertainty avoidance. There was a significant relationship between power distance and respondents’ desire for novelty on departmental and faculty lab websites. Collectivism, power distance, and uncertainty avoidance significantly predicted gratifications sought for realism, coolness, novelty, and being there on departmental and faculty lab websites. However, models with individual-level cultural dimensions explained only a small percent of variance for each gratification sought. While COAs should consider online search needs of prospective graduate students, individual-level cultural dimensions do not explain much of students’ preference for specific website characteristics. Future research should examine if the same is true across degree levels or disciplines outside of agriculture.
Keywords: graduate student recruitment; intercultural communication; uses and gratifications; online recruitment methods